Technology Adoption Of Millennial Generations In Implementation Of Self Ordering Machine In Fast Food Restaurant (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of technology that is very fast, encourage companies to implement technology that is the latest in the company so that the company's performance increases, especially a lot of consumers who are the generation of the millennial. The millennial generation is a generation that has tech savvy characteristics. One of the ways that is done by the company restaurant fast-food is to implement self-ordering machine. Self ordering machine is an innovation in the company's business process. Innovation that can provide convenience for customers to book menu and perform the payment as an independent. P Application of self-ordering machine for all customers on many generations of residence, may give rise to differences in readiness, because every generation has karakeristik are different. This study aims to determine the readiness to adopt Self Ordering Machine technology in the millennial generation when compared to the X generation. Readiness to adopt technology is based on the Unified Theory of Acceptance and Use of Technology (UTAUT). Results of the study showed that not there are differences in the readiness of the adoption of technology in the generation of millennials and the generation X.